Timing of chemotherapy-induced neutropenia predicts prognosis in metastatic colon cancer patients: a retrospective study in mFOLFOX6 -treated patients - Chen, Yang (BMC Cancer, 2017)
BACKGROUND: The occurrence of Chemotherapy-induced neutropenia (CIN) was reported to be a predictor of better survival in several cancers. The objective of our study is to evaluate the relationship between the timing of CIN and prognosis. METHODS: Between June 2012 and August 2014, 290 patients with confirmed metastatic colon cancer received at least one cycle of mFOLFOX6 as first-line chemotherapy were eligible for assessment as all patients group. Of the 232 received at least six cycles of mFOLFOX6 and survived 150 days after treatment were considered as landmark group. Timing of CIN was categorized into absence, early-onset and late-onset CIN groups. The end of cycle 3 was the cutoff to differentiate early-onset or late-onset. The correlation between timing of CIN with survival was analyzed by Kaplan-Meier method and Cox proportional hazards model. RESULTS: In all patients group, the median survival of patients without neutropenia, early-onset and late-onset neutropenia were 6.7, 20.7 and 12.8 months (P < 0.001). The patients with early-onset and late-onset CIN had better prognosis than CIN absence by multivariate analysis. Findings were much the same for landmark group. CONCLUSIONS: In conclusion, timing of CIN is an independent predictor of prognosis in metastatic colon cancer patients received mFOLFOX6, whereas an early-onset of CIN predicts longer survival.